Intervensi Non-Farmakologis untuk Menurunkan Fatigue ada Pasien Gagal Ginjal Kronik - Sri Alifia Anjani Yahya; Erida Fadila; Dwiyanti Purbasari (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Chronic kidney failure patients undergoing hemodialysis often experience fatigue that impacts physical, psychological, and quality of life. The treatment of fatigue does not only depend on pharmacological therapy, but can also be done through non-pharmacological interventions that are safer and have fewer side effects. This study aims to analyze the effectiveness of non-pharmacological interventions in reducing fatigue in hemodialysis patients. The research method uses Systematic Literature Review (SLR) with the PRISMA approach. Articles were obtained from Google Scholar, PubMed, ScienceDirect, and Garuda databases. A total of 11 articles that met the inclusion criteria were analyzed in depth. The results of the study showed that various non-pharmacological interventions such as relaxation therapy, exercise, acupressure, music therapy, and recreational therapy were proven to be effective in reducing fatigue and improving the comfort, sleep quality, physical capacity, and quality of life of hemodialysis patients. These findings confirm that non-pharmacological interventions can be used as complementary, safe, and effective companion therapies in clinical practice. The implications of this study provide a basis for health workers to integrate non-pharmacological interventions in the treatment program for patients with chronic kidney failure, so that it is expected to improve the overall quality of life.